Incentives for pollution control : regulation and(?) or(?) information - Foulon, Jérôme (Policy research working paper, 2000)
Both regulation and public disclosure belong in the environmental regulators' arsenal. Strong, clear standards combined with a significant, credible penalty system send the right signals to the regulated community, which responds by lowering pollution emissions. The public disclosure of environmental performance also provides strong additional incentives to pollution control